Graphics Out Loud: Perceptions and Strategic Actions of Students With Visual Impairments When Engaging With Graphics. (March 2022) - Zebehazy, Kim T.; Wilton, Adam P.; Velugu, Bhagyalaxmi
Introduction: Facility in graphics use is critical to accessing data visualizations in science, technology, engineering, the arts, and mathematics (STEAM) content areas. Efforts to understand the cognitive processes underlying strategic action by students with visual impairments must consider both metacognition and self-regulated learning.Methods: Think-aloud transcripts were analyzed using a priori level one coding based on the Model of Graphic Interpretation (MoGI) followed by second-level coding to analyze nuanced commonalities and differences based on performance, medium, and level.Results: Differences in each component of the MoGI were found for print graphic and tactile graphic users, particularly based on performance and level. Higher performers were better able to articulate strategy use and reasons for selecting strategies.Discussion: Findings coincide with quantitative findings of the participants (seeZebehazy & Wilton, 2021 ). Transcripts provided additional confirming evidence of the interdependence of MoGI components.Implications for Practitioners: Use of think aloud can support assessment and instruction of students with visual impairments to build strategic action and metacognition when engaging with graphics.